Earnings Quality and CEO Tenure - AHMAD AHMADPOR; ESMAT ESABAT TABARI; MEYSAM TALEBTABAR (پژوهش‌های تجربی حسابداری, 2015)
This study is aimed to examine the relation between earning quality and CEO Tenure of 83 firms listed in the Tehran Stock Exchange during 2004-2009. To test the hypothesis, Bal & shivakumar model of accruals as well as Basu model have been used. Findings show that CEOs with long tenures report have more aggressive reporting than CEOs with short tenures. These results suggest that CEOs with long tenures have more conservative reporting in the first half of their tenure than in the latter half.